PENGARUH PENGAWASAN AUDIT INTERNAL DAN PENGENDALIAN INTERNAL TERHADAP NILAI KKP - Astridyana Adriyanti; Titi Suhartati (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This research was motivated by a case study at the Ministry of Maritime Affairs and Fisheries (KKP), which received a disclaimer opinion, because there was an organizational structure that limited the authority of the role of internal auditors, thereby reducing the quality of financial reports. The research aims to examine the influence of internal audit supervision and internal control on the value of the Ministry of Maritime Affairs and Fisheries (KKP). This research uses an associative quantitative approach, and the sample selection uses purposive sampling techniques with specific criteria. Primary data was obtained from 41 respondents through distributing questionnaires. The data was tested and analyzed through the stages of descriptive analysis, data quality testing, classical assumption testing, and hypothesis testing. The results of this research show that there is a significant influence of internal audit supervision and internal control on the value of the Ministry of Maritime Affairs and Fisheries.